Dried bottom of Urmia Lake as a new source of dust in the northwestern Iran: Understanding the impacts on local and regional air quality - TAYANÇ, METE (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
Urmia Lake, the largest inland lake in Iran has lost most of its water surface area in the last 2 decades. The desertification caused by the drying of this unique lake may lead to dust storms from the lakebed and affect the air quality of the region. In this study, MODIS derived Aerosol Optical Depth (AOD) data observed between 2000 and 2019, Ultra Violet Aerosol Index (UVAI) data from Ozone Monitoring Instrument (OMI), meteorological data from MERRA-2 and ground-level PM10 data measured in the northwestern Iran and eastern Turkey were used to investigate the effects of the drying of Urmia Lake on local and regional aerosol pollution. The results revealed significant increase in aerosol pollution over the last 10 years. An inverse relationship was observed between water level fluctuations of Urmia Lake and aerosol pollution in the northwestern Iran. In total, 177 days (27 days in the period of 2000-2009 and 150 days in the period of 2010-2019) with mean daily AOD values equal to or greater than 1 were observed over the box covering Urmia Lake Basin (ULB). During 2000-2009, when the mean AOD was 0.25, the mean water surface area of the lake was observed to be 4000 km(2). When the lake dried up faster during 2010-2019 (the mean water surface area was observed 2100 km(2)), the mean AOD increased to 0.42. The eastern part of the lake was more polluted than western part due to the extent of salinization and desertification in this part and the prevailing wind direction from west to east. The results indicated similar trends with PM10 concentration in the northwestern Iran and eastern Turkey but the classification of PM10 values based on wind direction and wind speed rejected the influence of the lakebed on aerosol pollution in the eastern Turkey except in special meteorological conditions. These conditions occur when a low-pressure system over central Iraq and a high-pressure system located in a more northerly part of the region, mainly over the Caucasian, form a dust channel. In addition to dust storms from Iraq, Syria, Arabian Desert and local emission sources, the lakebed contributes as a new source of aerosol pollution mainly in the northwestern Iran and close regions.
Keywords: Urmia Lake; Dust emission; AOD; PM10; Aerosol pollution; Desertification; AEROSOLS; BASIN